Synthetic dataset of ID and Travel Documents - Carlos Boned; Maxime Talarmain; Nabil Ghanmi; Guillaume Chiron; Sanket Biswas; Ahmad Montaser Awal; Oriol Ramos Terrades (Scientific Data)
Abstract This paper presents a new synthetic dataset of ID and travel documents, called SIDTD. The SIDTD dataset is created to help training and evaluating forged ID documents detection systems. Such a dataset has become a necessity as ID documents contain personal information and a public dataset of real documents can not be released. Moreover, forged documents are scarce, compared to legit ones, and the way they are generated varies from one fraudster to another resulting in a class of high intra-variability. In this paper we introduce a dataset, synthetically generated, that simulates the most common, and easiest, forgeries to be made by common users of ID documents and travel documents. The creation of this dataset will help to document image analysis community to progress in the task of automatic ID document verification in online onboarding systems.